PENGARUH HARGA TERHADAP KEPUASAN KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA RUMAH MAKAN ANGKRINGAN 813 BEBEK BALURAN DI SITUBONDO - Riassta, Ilmi Yuli; Kusnadi, Edy; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2022)
In carrying out their wares, business people have advantages compared to other traders, for example in terms of the price of the menu offered, the quality of affordable prices can affect purchasing decisions and consumer satisfaction with the menu offered by the Angkringan Restaurant 813 Bebek Baluran in Situbondo Regency to attract consumer interest. . The purpose of this study was to determine the effect of price on consumer satisfaction with purchase decisions as an interening variable at Angkringan 813 Bebek Baluran Restaurant in Siubondo. This study used qualitative research methods. The population in this study were consumers of the 813 Duck Baluran Restaurant in Situbondo. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that price has a significant positive effect on consumer satisfaction, price has a significant positive effect on consumer satisfaction, purchase decisions have a significant positive effect on consumer satisfaction, consumer satisfaction has a significant positive effect on purchasing decisions